INCIDENTAL FINDINGS IN BIO BANKS IN SOUTH AFRICA: ETHICAL AND LEGAL ISSUES - Maureen Mswela; Patricia Molusi (Obiter, 2014)
Biobanks have come to be essential apparatuses of genetic and genomic research as they are seen as essential tools for translational medicine in particular. Various unique ethical and legal challenges arise in the course of biobanking as biobanks generate a range of ethical and legal challenges related to privacy, informed consent, control and ownership, withdrawal of samples, commercialization, genomic sovereignty, return of results, incidental findings, and research governance. These issues have generated much policy debate within the international world, and yet in South Africa, debates on the ethical and legal challenges posed by biobanks and biobank networks still remain alienated. According to Wolf, biobanks are the dominant part of a “biobank research system,” consisting of primary research also known as collection sites, the biobank, and secondary research sites that access biobank data or samples for further research. Therefore, incidental findings could arise at several points in a biobank-research system, that is, in primary research, biobank research, and secondary research. Within the South African context literature and guidance are sparse on the handling of significant incidental findings which are identified in biobank systems. How incidental findings should be handled as well as the role of biobanks in enabling this process, are well-founded concerns. Unresolved in South Africa, is how to manage incidental findings of potential health, reproductive, environmental and medicinal risk that are of particular importance to individual contributors. With a proposal for a national biobank in South Africa, it is apparent that researchers as well as clinicians are anticipated to access data from biobanks and to this end, laws, clear public guidance and regulations on the handling of incidental findings are indispensable.